Islamic Perspectives on Holistic Postpartum Care: Bridging Faith, Maternal Health, and Midwifery Practice - Marmi Marmi; Rina Nuraeni (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Background: The postpartum period represents a critical stage in maternal recovery that extends beyond physical healing to include psychological, social, and spiritual well-being. Although contemporary postpartum care has increasingly adopted evidence-based approaches, spiritual and religious dimensions remain insufficiently integrated into routine maternity services, particularly in Muslim populations. Methods: This narrative review synthesizes Islamic perspectives on postpartum care and examines their relevance to evidence-based midwifery practice. Results: The review discusses the Islamic understanding of postpartum (nifas), the ethical foundation of maternal care through maq??id al-shar?'ah, physical recovery, psychological and spiritual well-being, family support, and contemporary clinical issues, including postpartum contraception, sexual health, and religious-sensitive maternity care. Areas of scholarly disagreement and their implications for clinical decision-making are also examined to identify opportunities for integrating religious values with modern maternal healthcare. By bringing together Islamic principles and current evidence, this review provides a conceptual framework for holistic postpartum care that supports culturally responsive, woman-centred, and evidence-based midwifery practice for Muslim women.